Inhibitory Action of Antidiabetic Drugs on the Free Radical Production by the Rod Outer Segment Ectopic Aerobic Metabolism - Silvia Ravera; Federico Caicci; Paolo Degan; Davide Maggi; Lucia Manni; Alessandra Puddu; Massimo Nicolò; Carlo E. Traverso; Isabella Panfoli (MDPI AG, 2020)
Rod outer segments (OS) express the FoF1-ATP synthase and the respiratory chain, conducting an ectopic aerobic metabolism that produces free radicals in vitro. Diabetic retinopathy, a leading cause of vision loss, is associated with oxidative stress in the outer retina. Since metformin and glibenclamide, two anti-type 2 diabetes drugs, target the respiratory complexes, we studied the effect of these two drugs, individually or in association, on the free radical production in purified bovine rod OS. ATP synthesis, oxygen consumption, and oxidative stress production were assayed by luminometry, oximetry and flow cytometry, respectively. The expression of FoF1-ATP synthase was studied by immunogold electron microscopy. Metformin had a hormetic effect on the OS complex I and ATP synthetic activities, being stimulatory at concentrations below 1 mM, and inhibitory above. Glibenclamide inhibited complexes I and III, as well as ATP production in a concentration-dependent manner. Maximal concentrations of both drugs inhibited the ROI production by the light-exposed OS. Data, consistent with the delaying effect of these drugs on the onset of diabetic retinopathy, suggest that a combination of the two drugs at the beginning of the treatment might reduce the oxidative stress production helping the endogenous antioxidant defences in avoiding retinal damage.